Impact of video-led educational intervention on uptake of influenza vaccine among the elderly in western China: a community-based randomized controlled trial - Minghuan Jiang; Xuelin Yao; Pengchao Li; Yu Fang; Liuxin Feng; Khezar Hayat; Xinke Shi; Yilin Gong; Jin Peng; Naveel Atif (BMC, 2022)
Abstract Background Influenza vaccination coverage rate among the elderly is low in China. We aimed to evaluate the impact of video-led educational intervention on influenza vaccine uptake among the Chinese elderly. Methods A randomized controlled trial was conducted in 8 communities of Xi'an, a representative city in western China. Elderly aged over 60 years were randomized to the control group and intervention group (12-minute video education on influenza and its vaccination). Participants' knowledge, attitudes, and practices (KAP) of influenza was assessed by using a questionnaire survey before and after the intervention. The primary outcomes were participants' willingness to get influenza vaccinated and their actual uptake rates in the 2020-21 flu season. Secondary outcomes were the variations of pre- and post-intervention KAP scores. Intention-to-treat analysis was performed to analyze the data, and sensitivity analyses were conducted to examine the robustness of the results. Results A total of 350 people were enrolled, with 175 individuals for each group. Participants in the intervention group were more willing to receive influenza vaccination than those in the control group (64.6% vs. 51.4%, p<0.05). The influenza vaccination uptake rate occurred in 10.3% of participants in the intervention group and 3.4% in the control group (odds ratio, 3.23; 95% CI 1.25-8.32, p<0.001). The post-intervention KAP scores in the intervention group were significantly higher compared to those in the control group (p<0.001). Conclusion Video-led education was an effective and feasible approach to improve old people's willingness and uptake of influenza vaccination in western China.